Dawn of the dead - Synder, Zack (Universal Studio, 2004)
The planet's population is hit by an inexplicable, unfathomable and lethal plague - and the dead aren't staying dead. Corpses yearning for their next meal are now stalking the few remaining survivors to feed on their flesh. The few survivors - one of the last bastions of humanity - take refuge in an abandoned suburban mall. Here they pool resources to fight to stay alive - and most important human. A re-envisioning of George A. Romero's Apocalyptic horror classic.